The role of teaching approaches in enhancing student retention: An assessment of student satisfaction at a comprehensive university in the Eastern Cape - Stofile, Regina; Enwereji, Prince Chukwuneme (Edelweiss Applied Science and Technology, 2025)
This study investigates students' perceptions of teaching approaches and their impact on satisfaction within a higher education institution in South Africa. The study adopted Tinto’s model of student engagement, which emphasizes the significance of academic and social integration in fostering student commitment and success. A total of 660 third-year students, selected through stratified random sampling, participated in the study. Data were collected using structured questionnaires to capture students' opinions on various teaching methods and satisfaction levels. The Statistical Package for Social Sciences was used to analyze the data. The findings revealed a significant positive relationship between teaching approaches and student satisfaction, with teaching approaches accounting for 68% of the variation in satisfaction. The study emphasizes the importance of both teacher-centered and student-centered teaching strategies in enhancing engagement and satisfaction. It recommends the adoption of innovative and flexible pedagogical approaches tailored to address diverse student needs. Institutions are advised to address campus-specific disparities and ensure equitable teaching quality. The study further emphasizes that fostering strong student-teacher relationships and providing ongoing professional development for educators are critical for improving teaching effectiveness and student outcomes. These insights are vital for creating supportive learning environments that enhance student satisfaction and promote academic success.